Comparison of Pre-Loading Fluid With Norepinephrine Toward Mean Arterial Pressure (MAP) In Sepsis Patients In Intensive Care Unit (ICU) of Haji Adam Malik General Hospital, Medan: Pre-Loading Fluid With Norepinephrine - Sidiq, Rendi; Lubis, Bastian; Solihat, Yutu (Journal of Society Medicine, 2022)
Introduction: Sepsis is a life-threatening organ dysfunction caused by dysregulation of the host response to infection. Sepsis and septic shock are major health problems, affecting millions of people worldwide each year and killing one in six people affected. Early identification and appropriate management in the early hours after the development of sepsis improves the patient's prognosis. Surviving Sepsis Campaign (SSC) 2021 recommends a fluid dose of 30mL/kgBW, but there are many studies stating that there is no difference in patient outcomes when we resuscitate patients with 10 or 20 mL/kgBW fluids. Norepinephrine is considered as the safest and most potent vasopressor agents than others. Methods: This study used a double-blind randomized clinical trial (RCT) design to assess MAP in sepsis patients in intensive care unit (ICU) of Haji Adam Malik General Hospital ,Medan. Results: There were more male (56.5%), than female (43.5%). In our study, administration of 10mL/kg and 20mL/kg fluid bolus with vasopressor resulted in increased MAP, and the differences were statistically significant (p < 0.05). Administration of 10 mL/kg fluid gave higher MAP values than the other groups, could be a consideration in choosing fluid in order to avoid fluid overload. Conclusion: There is a significant comparison in the ratio of norepinephrine pre-loading fluid toward MAP in sepsis patients. Comparison of the mean MAP value at 15, 20, 25 minutes was the highest in the 10 mL/KgBW group. Meanwhile, the lowest MAP was found in 30mL/KgBW the group.